WHAT ROLES DO INDONESIAN NURSES PLAY IN THE EARLY IDENTIFICATION AND INTERVENTION OF CHILDREN WITH DEVELOPMENTAL DISABILITIES? A QUALITATIVE STUDY - Mardiyanti Mardiyanti; Lesley Cuthbertson; Paul Jewell (Belitung Raya Foundation, Indonesia, 2020)
Background: Developmental delays can be a basis for identifying children who may experience a disability. Accordingly, developmental screenings and monitoring are implemented to facilitate early identification of developmental disabilities Objective: To explore Indonesian’s community nurses’ perceptions regarding their roles in the early identification and intervention of developmental disabilities Method: This was a descriptive phenomenological study. Eleven community health nurses participated in a multiple semi-structured interview. Thematic analysis was used to analyse data. Findings: Four themes of nursing roles emerged, these include parents’ expression of need, a focus on curative management, provision of nursing care and being alert to discuss a possible developmental delay. Indonesian nurses describe their roles as focusing on curative management and include monitoring child growth and nutritional status because they perceive these roles as the main program of the centres and as to fulfilling parents’ expressions of needs, however they will raise concern when it is suspected or observed, that the child has delayed development. Conclusion: Child’s developmental surveillance has been implemented in developed countries as the basis to identify developmental disabilities earlier in children, however Indonesian nurses focus more on nutrition and eradicating communicable diseases rather than child’s developmental monitoring. More investigation is needed to find barriers of implementation of developmental screenings.